Strategi Kepemimpinan Kepala Sekolah Dalam Menerapkan Pendidikan Karakter Bagi Siswa - mustajib; Miksan Ansori (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
Leadership is a conscious effort made by a person (leader) to be able to realize the goals of the organization through others by providing motivation so that others will carry it out, and therefore there is a need for a balance between the individual needs of the implementers. A leader must understand and understand the basics of leadership in order to be a leader, both in a small sphere, such as families, discussion leaders, etc. and leaders in large scopes such as organizational leaders, religious leaders, state leaders and so on. But there are several factors of leadership emergence: first, situation and condition factors; second, the capability factor; third, hereditary factors; fourth, the lifting factor; fifth, the importance factor. In the world of education, the Principal in developing character education plays an important and crucial role because it becomes a policy determinant and director in the implementation of character education in schools. As the implementation of the president's policy on character education in various agencies and thoroughly in the life of the nation and the state, as educators and school leaders must participate in realizing the nation's children with character. To get clear data, the authors used observation methods, documentation and interviews. While this type of research is field research using qualitative approach. The object of the research is the Principal Leadership Strategy in Developing Character Education for Students at SMK Ma'arif NU Pare. The subjects of this study were the principals of SMK Ma'arif NU Pare, Teachers, and also Students.